The development of correlation log - Horwitz, Adrian Miles (Department of Electrical Engineering, 2017)
A measure of ship speed is needed for dead reckoning navigation, docking, and as an input to satellite navigation systems. Ship speed is also used as an input to fire control systems on Naval vessels. The need for an accurate speed measuring device, that measures ship speed relative to the sea bed is thus apparent. All non acoustic logs measure ship speed relative to the water, and absolute ship speed can only be estimated if a knowledge of water currents is available. An acoustic log that provides an absolute measure of ship speed at limited operating depths is the Doppler log. For deep water the Doppler log measures speed relative to the water and it is thus affected by currents. A new development in acoustic logs is the correlation log. The correlation log can measure absolute speed at much greater depths than can the Doppler log. This is because it utilises a wide beam pointing vertically at the sea bed. The.wide beam permits a low operating frequency to be used which implies low attenuation. The high backscattering strength at normal angles of incidence combined with the low attenuation, means that relative to the Doppler log, the correlation log can measure absolute speed at much greater depths. The correlation log consists of a transmitter, which utilises tone burst transmission, and two or more receivers in line with the direction of motion. The signals received by two transducers will be similar except for a time shift 'T', which is given by the equation T = d/2V, where V is the speed and d the transducer separation. A device based on these principles has been built and tested. Results have shown that the system concepts are viable and will lead to an absolute speed measuring device that can operate at great depth.